2008
DOI: 10.1002/ccd.21468
|View full text |Cite
|
Sign up to set email alerts
|

Late percutaneous coronary intervention for the totally occluded infarct‐related artery: A meta‐analysis of the effects on cardiac function and remodeling

Abstract: This meta-analysis suggests that late revascularization of an occluded IRA may improve left ventricular systolic function and remodeling, supporting the "open artery hypothesis." The reason why these changes have not resulted in clinical benefits in large clinical trials is subject to debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
3
19
0
2
Order By: Relevance
“…Several trials in the stent era and several meta-analyses have examined the role of PCI for fibrinolytic failure 346,[355][356][357]364 (Online Data Supplement 4). These studies report a trend toward a lower mortality rate and significantly lower rates of recurrent MI and HF among patients treated with rescue PCI for failed fibrinolysis.…”
Section: Transfer For Failure Of Fibrinolytic Therapymentioning
confidence: 99%
“…Several trials in the stent era and several meta-analyses have examined the role of PCI for fibrinolytic failure 346,[355][356][357]364 (Online Data Supplement 4). These studies report a trend toward a lower mortality rate and significantly lower rates of recurrent MI and HF among patients treated with rescue PCI for failed fibrinolysis.…”
Section: Transfer For Failure Of Fibrinolytic Therapymentioning
confidence: 99%
“…Сравнительный анализ результатов ПЭТ и МРТ сердца показал, что прогностическая ценность обоих методов зависела от степени тяже-сти анатомического повреждения сердечной мышцы. ОПЦ МРТ с использованием критерия "объем рубца" была существенно выше, чем у одно-изотопной ПЭТ с 18 F-ФДГ и сочетанного исследо-ных осложнений и улучшению долгосрочного про-гноза заболевания [14,15]. Заключение Магнитно-резонансная томография сердца с большей точностью предсказывает улучшение реги-онарной функции ЛЖ после эндоваскулярной река-нализации ХОКА.…”
Section: оригинальные статьиunclassified
“…10,11 It should be appreciated that a number of recent studies have reported results contrary to those reported by the OAT study in this issue of Circulation. 12,13,14 A meta-analysis of 10 randomized trials included 3560 patients. There were 648 patients with total occlusion of the infarct-related artery.…”
Section: Article See P 2724mentioning
confidence: 99%